Práticas de letramentos na educação de jovens e adultos por meio do gênero discursivo autobiografia - Martins, Edilson Barbosa (2021)
According to official documents, Youth and Adult Education as a teaching modality assumes the role of repairing and granting equal opportunities, giving access to goods such as reading, writing and orality to those who were unable to enjoy it in the past, replacing it. those as able to participate effectively in the literate and graphocentric society. In this context, it is imperative that the teaching practices developed for this modality include writing as a focus, without disregarding the reading and orality that permeate all activities, and that these be put in a meaningful way, based on the real uses that are it does in the various social spheres, effectively constituting literacy practices. Thus, this work had the intention, from a diagnosis, to conceive a literacy project involving the discursive genre autobiography and others, which could contribute both to the improvement of the writing process, as well as to a better insertion in the literate culture of the students. Youth and Adult Education, 2nd Cycle of Elementary Education, from a public school in the municipality of Santa Rita-PB. In this sense, qualitative research was developed, configured as an exploratory research, whose data collection instruments were a set of diagnostic activities and questionnaires, in addition to the application of the informal conversation methodology, used remotely. As a technique for analyzing the data obtained, we take the content analysis, supported by Bardin (1977). It is understood that such instruments and methodology for data generation and analysis helped to support the proposals that were made with a focus on the discursive genre autobiography, taken to promote literacies. The theoretical construction used brings the understanding of Brazilian legislation regarding EJA as the Law of Directives and Bases of National Education (BRAZIL, 1996), the Curricular Guidelines for the Education of Youth and Adults (BRAZIL, 2000) and the Common National Base Curricular (BRASIL, 2018), as well as the understanding of authors, among which are: Gadotti and Romão (2000); Paiva; Machado and Ireland (2007) and Gadotti (2008). With regard to the understanding of literacy practices Tfouni (2005), Oliveira, Tinoco and Santos (2014), Kleiman (1995, 2000, 2005, 2007), Rojo (2009) and Soares (2017); Bakhtin (2003), Koch and Elias (2014) corroborate writing as a discursive interaction and with regard to the discussion around the discursive genre autobiography, Larrosa (1994), Cunha (1997), Belon and Maciel (2004), Lejeune (2014), among others. The analysis of the data allowed the understanding of the desires and perspectives put through the voices of the researched subjects, taken as a starting point for proposing a set of activities that were configured as a literacy project. Therefore, working with writing as a focus, but without also disregarding reading and orality intertwined with the possibilities of activities addressed, it is expected to contribute so that the educational process developed at EJA can help in improving students' communicative competence, translating itself better exercise of citizenship.